Antiphospholipid antibodies in patients with myocardial infarction with and without obstructive coronary arteries. (24th November 2021) - Svenungsson, Elisabet; Spaak, Jonas; Strandberg, Karin; Wallén, Håkan N.; Agewall, Stefan; Brolin, Elin B.; Collste, Olov; Daniel, Maria; Ekenbäck, Christina; Frick, Mats; Henareh, Loghman; Malmqvist, Karin; et al.
Abstract: Background: Recent studies demonstrate that prothrombotic antiphospholipid antibodies (aPL) are overrepresented in patients with myocardial infarction (MI) due to coronary artery disease (MICAD). However, it is not known whether aPL differ between the two subsets of MI: MICAD and MI with nonobstructive coronary arteries (MINOCA). Objectives: To determine whether aPL are associated with MINOCA or MICAD, or with hypercoagulability as assessed by activated protein C–protein C inhibitor (APC–PCI) complex. Methods: Well‐characterized patients with MINOCA ( n = 98), age‐ and gender‐matched patients with MICAD ( n = 99), and healthy controls ( n = 100) were included in a cross‐sectional case–control study. Autoantibodies (IgA/G/M) targeting cardiolipin and β2 glycoprotein‐I and specific nuclear antigens were analyzed by multiplexed bead technology. The concentration of APC–PCI was determined as a measure of hypercoagulability by an immunofluorometric sandwich assay. Results: Both prevalence and titers of aPL of the IgG isotype (anti‐cardiolipin and/or anti‐β2 glycoprotein‐I) were higher in patients with MINOCA and MICAD than in controls. aPL IgG positivity was twice as frequent among patients with MICAD than MINOCA (11% vs. 6%, nonsignificant). We observed no group differences regarding aPL IgA/M or antibodies targeting specific nuclear antigens. Levels of APC–PCI were elevated in aPL IgG‐positive compared to aPL IgG‐negative MICAD patients. Conclusions: aPL IgG, but not IgA/M, are enriched particularly in patients with MICAD but also in patients with MINOCA, as compared to controls. Interestingly, signs of hypercoagulability—measured by increased levels of the APC–PCI complex—were present in aPL IgG‐positive MICAD patients, indicating an association with functional disturbances of the coagulation system. Abstract :